Caries experience associated to social and preventive factors in children of a pastoral community from Limeira-SP - Ferraz, Maria Julia Pereira Coelho; de Paula Queluz, Dagmar; Alves, Marcelo Corrêa; dos Santos, Carla Cristina Gonçalves; Matsui, Miriam Yumi [UNESP] (My University, 2011)
Aim: To evaluate caries experience and prevalence associated to social and preventive factors in 3-6-year-old children of a Pastoral Community from Limeira, Brazil. Methods: A cross-sectional study was carried out through an epidemiologic research about the oral conditions of 110 children registered at the Children's Pastoral Community from the city of Limeira, SP, Brazil. Intraoral examination was performed by a trained dentist and the parents/caregivers filled out a questionnaire in order to outline the children's profile with respect to gender, parental education and oral health. Results: Differences related to gender were not detected (p= 0.3404). The most frequent periods of breastfeeding were 0 to 2 months (36.36%) and 2 to 6 months (35.45%), corresponding to 71.81% of the cases. The time bottle feeding pointed to two most frequent categories: 1) more than 12 months (35.45%) and 2) between 2 and 6 months (22.63%). Regarding parental education, the majority of the sample has not completed primary school (38.32%). It was observed a larger number of decayed teeth in male children (63.39%). Caries experience was significantly higher in children who were breastfed for only 2 months of life (41.96%). Children that did not use baby bottle or did not use a baby bottle for more than 1 year presented a smaller dmft, corresponding to 29.17% and 28.33%, respectively. Time of use of bottle and pacifier presented a significant association (p<0.05). Conclusions: The implementation of adequate strategies and actions is needed to reinforce oral health conditions in risk groups.
Keywords: Dental caries; Dental health surveys; Dmft index; Epidemiology; Health promotion; Oral health; School health services